2021
DOI: 10.1111/jocs.15376
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Predictors of postoperative adverse events after cone reconstruction for Ebstein's anomaly

Abstract: Prediction scores and metrics are being increasingly utilized throughout the fields of cardiothoracic and congenital cardiac surgery to identify areas for perioperative optimization or guide therapeutic intent. Here, we review a novel submission by Yang and colleagues to the Journal of Cardiac Surgery identifying preoperative factors that predict adverse postoperative outcomes from cone reconstruction for Ebstein's anomaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…In accordance with our findings, Ibrahim et al, using serial echocardiographic assessment of RV function, showed improved RV systolic function after 24 to 36 months of surgery and hypothesized that the eradication of TR and improved forward flow in the pulmonary artery could present as enhanced RV myocardial performance several years after the repair (23). It has been noted that tricuspid regurgitation is remarkably reduced after cone reconstruction; however, RV function typically takes longer to improve (24). The present research revealed a statistically significant increase in LVEF and a decline in LVEDD; however, LVESD remained unchanged.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with our findings, Ibrahim et al, using serial echocardiographic assessment of RV function, showed improved RV systolic function after 24 to 36 months of surgery and hypothesized that the eradication of TR and improved forward flow in the pulmonary artery could present as enhanced RV myocardial performance several years after the repair (23). It has been noted that tricuspid regurgitation is remarkably reduced after cone reconstruction; however, RV function typically takes longer to improve (24). The present research revealed a statistically significant increase in LVEF and a decline in LVEDD; however, LVESD remained unchanged.…”
Section: Discussionsupporting
confidence: 92%
“…However, cardiovascular magnetic resonance analysis showed that cone reconstruction improved LV filling due to the enhanced forward blood flow following a significant reduction in TR severity (23). Moreover, Rotar and Kron found no changes in the left-sided ejection fraction, global circumferential, and longitudinal strains (24). However, basal septal circumferential strain improved with a median of 2.8 years after cone reconstruction.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation